The Effect of Self-Efficacy On Students’ Learning Outcomes In Islamic Religious Education - Apriliana Apriliana; Tuti Alawiyah; Abu Bakar (Fakultas Agama Islam, 2025)
This study aims to analyze the influence of self-efficacy on the learning outcomes of Islamic Religious Education (PAI) among eighth-grade students at SMP IT Ar-Rasyid STM Hilir. The research background arises from the phenomenon of varying levels of students’ self-confidence, which impacts their engagement and academic achievement. A quantitative approach with a survey method was employed to measure self-efficacy using a Likert-scale questionnaire, supported by interviews, observations, and documentation of learning outcomes. The population consisted of 94 students, all included as the research sample through saturated sampling. The instrument was tested for validity and reliability using SPSS, yielding a Cronbach’s Alpha of 0.896. Data were analyzed using descriptive and inferential statistics with Spearman’s rho correlation test. Findings revealed that most students had moderate to high self-efficacy, with an average score of 67.73. The average PAI learning outcome was 82.79, categorized as good. The correlation test produced a significance value of 0.044 and a correlation coefficient of 0.208, indicating a positive but low significant relationship between self-efficacy and learning outcomes. These results highlight self-efficacy as an important psychological factor supporting PAI learning success, though outcomes are also influenced by motivation, environment, and teaching methods.